Proposal of a Technical Model of Soccer Kicking: A Systematic Review of Kinematic and Kinetic Variables - Aedo-Muñoz, Esteban (2020)
This article describes a propositive vision of the current literature on soccer kicking techniques. It aims to identify the potential kinetic and kinematic variables used in the analysis of the techniques, and to determine the values of kinetic and kinematic variables in relation to the kicking techniques in soccer. PubMed and Taylor & Francis online were reviewed to obtain selected articles from 2000 to 2017. PRISMA® methodology was implemented. Twenty-nine papers were selected; they considered kicking techniques in soccer young or adult participants through biomechanical variables. Then, a four-phase technical model was prepared: preparation, roll, impact, and follow-up phases. A technique-based biomechanical perspective can offer a promising strategy to improve, from training and technique analysis, the performance in football, in addition to providing a background for injury prevention.